The existence of Lead, tin and arsenic in foodplants grown at the Son Duong tin mine area, Tuyen Quang province - Hong Van, Luong Thi; Minh, Do Thi (Academia Journal of Biology, 2014)
The authors researched on the existence of lead (Pb), tin (Sn) and arsenic (As) in food plants (vegetables, tubers, fruits), which were growned at the of Sonduong tin mine area, Tuyenquang province. The results showed that the contents of Pb and As in food plants grown at the Sonduong tin mine area were higher than the ones in allowed criteria and also higher than the ones in the control area from 4 to 6 times (for Pb) and from 4 to 17 times (for As). The content of Pb was normal in all groups. There was a tight correlation betweem the contents of Pb and the ones of As and Sn in vegetables, which were used as foods for natives lingving in the Sonduong tin mine area, Tuyenquang province (r = 0.4-0.9; p < 0.01).